Effect of Pretreatment and High Hydrostatic Pressure on Soluble Dietary Fiber in Lotus Root Residues - Yanyang Gu; Liying Niu; Jiangfeng Song; Chunju Liu; Zhongyuan Zhang; Chunquan Liu; Dajing Li; Lixia Xiao (Journal of Food Quality)
High hydrostatic pressure (HHP) can enhance the physicochemical properties of soluble dietary fiber (SDF) from fruit and vegetable residues including hydration properties, emulsibility, and rheological properties, while the pretreatment methods such as solid-water suspension status are ignored all along. Here, three groups of lotus root residue (LRR) for HHP treatment (400 MPa, 15 min) were prepared: the fresh lotus root residue (FLRR), FLRR mixed with water (FLRR + W), and dried FLRR suspended in water at the same solid/water level with FLRR + W (DLRR + W). As a control, non-HHP-treated FLRR was tested. Results showed that FLRR + W obtained the highest SDF yield and presented a honeycomb structure which was not observed in other LRR samples. In addition, properties of SDF extract from FLRR + W changed most significantly, including not only the enhancement of SDF yield, the improvement of hydration properties, and the reduction of molecular weight but also the increase of thermal and rheological stability. Principal component analysis (PCA) profile illustrated that the difference of LRR-water system contributed 27.6% to the SDF physicochemical changes, and SDF from DLRR + W distinguished it from the other samples with mannose, ribose, and glucuronic acid, indicating that the drying procedure also played a role in the HHP treatment focusing on the sugar constitution. Therefore, the solid-water suspension status is a noteworthy issue before HHP treatment aiming at SDF modification.